Organizational Justice and Social Capital in Increasing Satisfaction and Commitment: Notes and Reviews - Hermawan, Hermawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Among several literatures that discuss organizational justice, research by Tjahjono et al. (2019) is a quite interesting study because it analyzes individual factors, namely social capital in the relationship between organizational justice and satisfaction and commitment. Based on a search through the publish or perish software, the Scopus-indexed research linking organizational justice and social capital from 2019 to 2020 is only research by Tjahjono (2019). Therefore, research related to organizational justice and social capital needs to be developed and explored again. This research is a critical review that specifically provides notes and reviews in articles written by Tjahjono (2019). The results of this study provide several notes that include recommendations for measuring variables that can be carried out by further researchers in discussing organizational justice, social capital and satisfaction. Furthermore, this study provides notes on research methods to be more in-depth as well as notes related to research results. It is hoped that this research can deepen discussions related to organizational justice, social capital and satisfaction and commitment. This research is also expected to be a reference in further research related to organizational justice and social capital.